Titanium Surface Properties Influence the Biological Activity and FasL Expression of Craniofacial Stromal Cells - Enrico Conserva (Stem Cells International, 2019)
Mesenchymal stromal cells (MSCs) can be easily isolated form craniofacial bones during routine dentistry procedures. Due to their embryological origin from neural crest, they represent a suitable cell population to study cell-biomaterial interaction in the craniofacial field, including osteoinductive/osteointegrative processes. The biological and immunomodulatory properties of MSCs may be influenced by chemistry and topography of implant surfaces. We investigated if and how three different titanium surfaces, machined (MCH), sandblasted with resorbable blasting medium (RBM), and Ca++-nanostructured (NCA), may affect biological activity, osseointegration, and immunomodulatory properties of craniofacial MSCs. Cell proliferation, morphology, osteogenic markers, and FasL were evaluated on MSCs isolated from the mandibular bone after seeding on these three different surfaces. No statistically significant differences in cell proliferation were observed whereas different morphologies and growth patterns were detected for each type of surface. No difference in the expression of osteogenic markers was revealed. Interestingly, FasL expression, involved in the immunomodulatory activity of stem cells, was influenced by surface properties. Particularly, immunofluorescence analysis indicated that FasL expression increased on MCH surface compared to the others confirming the suggested role of FasL in promoting osteogenic differentiation. Titanium surface treatments and topography might reflect different biological behaviours of craniofacial MSCs and influence their osseointegration/immunomodulation properties.